Effects of extracellular vesicles released by peritoneal B‐1 cells on experimental Leishmania (Leishmania) amazonensis infection. Issue 6 (30th April 2020) - Toledo, Maytê dos Santos; Cronemberger‐Andrade, André; Barbosa, Fernanda Marins Costa; Reis, Natasha Ferraz de Campos; Dupin, Talita Vieira; Soares, Rodrigo Pedro; Torrecilhas, Ana Claudia; Xander, Patricia
Abstract: B‐1 cells are a B‐lymphocyte subtype whose roles in immunity are not completely defined. These cells can produce cytokines (mainly IL‐10) and natural and specific antibodies. Currently, extracellular vesicles (EVs) released by immune cells have emerged as new important entities in cell‐cell communication. Immune cells release EVs that can activate and/or modulate other immune cells. Here, we characterized the EVs released by peritoneal B‐1 cells infected or not with Leishmania ( Leishmania ) amazonensis . This Leishmania species causes cutaneous leishmaniasis and can infect macrophages and B‐1 cells. Our results showed that peritoneal B‐1 cells spontaneously release EVs, but the parasite stimulated an increase in EVs production by peritoneal B‐1 cells. The treatment of BALB/c and C57BL/6 bone marrow‐derived macrophages (BMDM) with EVs from infected peritoneal B‐1 cells led to differential expression of iNOS, IL‐6, IL‐10, and TNF‐α. Additionally, BALB/c mice previous treated with EVs released by peritoneal B‐1 cells showed a significant lower lesion size and parasite burden. Thus, this study demonstrated that peritoneal B‐1 cells could release EVs that can alter the functions of macrophages in vitro and in vivo these EVs altered the course of L. amazonensis infection. These findings represent the first evidence that EVs from peritoneal B‐1 cells can act as a new mechanism of cellular communication between macrophages and B‐1 cells, contributing to immunity against experimental leishmaniasis. Graphical Abstract: EVs from peritoneal B‐1 cells contribute to immunity against experimental leishmaniasis